ANALISIS EFEKTIVITAS UPTD BALAI LATIHAN KERJA (BLK) DISNAKER KOTA SEMARANG DALAM MENINGKATKAN KETERAMPILAN MASYARKAT KOTA SEMARANG - M.Fajar Asshiddiq Simatupang; Purwoko .; Nunik Retno Herawati (Journal of Politic and Government Studies, 2017)
Poverty  happens in many areas  in  Indonesia  is  a classic  problem, as poverty will trigger a crime or criminality,because indeed human resource needs to survive  hence the  need for  training and the coaching job for the community.Work Practice UNIT BLK formed Government in effort to overcome poverty and unemployment in the Semarang City with infrastructures and training  places to get skills or who want to deepen their expertise in their fields . This research is a policy studies analyzing the effectiveness of  UNIT  BLK  and  efforts made Semarang Government in running the training program with qualitative descriptive  methods. This research was conducted in Semarang City, Central Java. With the techniques of data collection through interview  and documents.In the implementation of a training program  in  UNIT  BLK  Disnaker  Semarang city researchers found factors that affect success rate of good facility or infrastructure in the process including job training efforts that have been undertaken by Governments. As well as the researchers found effectivity variables of an organization that has not been fulfilled and affect the effectiveness of an organization. Especially in these research, findings one is the lack of permanent trainers and training material that have not been in accordance with the times, which need the ability and expertise to continue to increase. Recommendations of researchers need to  immediately  recruit  instructors  remain and have been officially  training as well as the need to enhance cooperation  with  private parties both companies and so on, in order to improve the learning  material  that suit the market needs, as well as the training of graduates who have  made the standards of  good competence. Keywords: poverty, effectiveness, Organization, policies